2014
DOI: 10.1074/jbc.m113.515759
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Defects in Mice Expressing the L68Q Variant of Human Cystatin C

Abstract: Background: The L68Q variant of cystatin C is highly amyloidogenic forming aggregates in individuals with HCCAA. Results: Spermatozoa from mice expressing human L68Q cystatin C exhibit fertility defects and increased levels of amyloid. Conclusion: L68Q epididymal fluid containing cystatin C amyloid is harmful for sperm function. Significance: Amyloid in the reproductive tract may contribute to male factor infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…These deposits are mainly composed of the L68Q hCC variant, which shows a naturally high potential for dimerization and self‐association, and is highly amyloidogenic . Further experiments indicated that the presence of L68Q hCC in epididymal fluid may damage mice spermatozoa and reduce male fertility . Therefore, while the structure of monomeric hCC serves as a first goal toward understanding the protein's interactions with proteases, higher order oligomer structures appear to play a role in some diseases associated with hCC.…”
Section: Understanding Hcc Monomer Structurementioning
confidence: 99%
“…These deposits are mainly composed of the L68Q hCC variant, which shows a naturally high potential for dimerization and self‐association, and is highly amyloidogenic . Further experiments indicated that the presence of L68Q hCC in epididymal fluid may damage mice spermatozoa and reduce male fertility . Therefore, while the structure of monomeric hCC serves as a first goal toward understanding the protein's interactions with proteases, higher order oligomer structures appear to play a role in some diseases associated with hCC.…”
Section: Understanding Hcc Monomer Structurementioning
confidence: 99%
“…As the most abundant protein, Cst C was found in tissues outside of the brain including the testis, and so was the L68Q variant 70 . A recent study reports that heterozygous transgenic mice that express this pathogenic variant were unable to generate offspring, indicating the L68Q Cst C amyloid affects sperm function 71 . Further analysis of the L68Q mice demonstrated that their epididymal spermatozoa were unable to fertilize oocytes and exhibited poor sperm motility in the presence of Cst C amyloid that were not found in the wild‐type mice.…”
Section: Pathophysiological Roles Of Cst Cmentioning
confidence: 99%
“…It is primarily divided into three regions, namely caput, corpus, and cauda. are localized on the sperm surface and aid in sperm maturation and function (Li et al, 2001;Hall et al, 2002;Narmadha et al, 2011;Srakaew et al, 2014;Whelly et al, 2014;Narmadha & Yenugu, 2016). During the transit in this organ system, spermatozoa acquire motility and fertilizing ability and this is thought to be achieved because of their interaction with a wide variety of proteins secreted by epithelial cells.…”
Section: Introductionmentioning
confidence: 99%